When images hurt hyper-reality and symbolic violence in Indonesian men’s lifestyle magazines - Desi Dwi Prianti (Cogent Social Sciences)
In Western culture, the practice of looking has traditionally been perceived as an act of dominance. Enacted by the male gaze, looking implies an active position, whilst to be looked at implies a passive position. However, in the case of Indonesian men’s lifestyle magazines, these practices of looking fuel the internalisation of inferiority on the part of Indonesian subjects. Emerging from its colonial past, contemporary Indonesia continues to be confronted with a persistent colonial order of things—an imaginary structure that is highly hierarchical and rooted in the colonial legacy. Notably, this colonial discourse also impacts men and masculinity. By analysing seven different men’s lifestyle magazines spanning the period from the earliest magazines published in the mid-1970s until 2015 and providing analyses of other sociocultural practices in Indonesian society, in this article I interrogate the internalisation of this colonial discourse and the symbolic violence that Indonesians enact upon themselves in the process. In order to untangle the deep-rooted and complex inlander mentality marked by colonialism, I demonstrate how doxa, in the form of hyper-reality, produce symbolic violence between spectators and spectacles.